Pengambilan Keputusan Bercerai Tokoh Kinan Pada Web series Layangan Putus Ditinjau Dari Psikologi Dan Hukum Islam - Betty Prastiwi; Arih Merdekasari (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2024)
Abstract: The research aims to find out how the decision to divorce the character Kinan in the web series Kite Putus is viewed from psychology and Islamic law. The research method uses a qualitative approach in the study of Cyberliterary Psychology. The research was carried out by watching the web series to be analyzed descriptively and inductively, then created in the form of text and analyzed. Descriptive analysis describes the aspects and characteristics of the message, while inductive analysis is used to understand and examine the meaning. The data source was obtained from the rater through a questionnaire that met the gender requirements of female, Islamic religious education student and early adulthood. Next, the data was validated through an inter-rater test. Kinan's character's psychological decision-making process goes through five stages. First, assess the challenges stemming from the phenomenon of changes in her husband's attitude which gives rise to confusion and suspicion, then encourage her to collect data and information to find the reasons for the change in her husband's attitude. Second, an alternative survey regarding the findings of physical evidence and information originating from Kinan's friends and people around Aris, which leads to proof of her husband's infidelity. Third, consider alternatives by carrying out a negative evaluation of the loss of hope of forming a harmonious family and the opportunity to live a new life while maintaining one's self-esteem. Fourth, declare your commitment, express your stance by suing Aris in court while continuing to consult with friends who are competent in the legal field. Also, keep sharing with friends who can provide in-depth insight into the correct attitude in dealing with developments in family problems. Fifth, survive negative feedback, face her husband's negative attitude by continuing to manage negative emotions and focus on gathering evidence that clarifies her husband's commitment to polygamy. Meanwhile, the Kinan character's decision to divorce in terms of Islamic law is permissible because it meets the requirements for being included in the Fasakh case or not. can be corrected again because Aris' behavior violates Islamic religious law as stated in the Al-Quran surah An-Nur verses 30-31. The problems include infidelity and quarrels which cause her to not be able to get back together with her husband. Keywords: Cybersastra, Decision making, Islamic law, Psychology, Web series.